ANALISIS TINGKAT PENDIDIKAN, SKALA USAHA, PENDAPATAN USAHA DAN PENGALAMAN USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA PELAKU UMKM DI KOTA BATAM - Neni Marlina Br Purba; Khadijah Khadijah (JURNAL MUTIARA AKUNTANSI, 2020)
This research was conducted to find out how the influence was given to the use of accounting information through the level of education, business scale, business income and business experience by MSME players in Batam City. The research is quantitative and the data is primary data in the form of a questionnaire used. All UMKM players in Batam city that are registered in the cooperative and the UMKM office in Batam city are the object or population. Samples were taken by simple random sampling and using the Slovin formula. The data analysis method used is validity test, reliability test, classical assumption, descriptive analysis, multiple linear regression and hypothesis testing. By using the SPSS test, the results of the t test for the level of education, business scale and business income have a significant effect on the use of accounting information, while business experience has no significant effect. Through the f test, the education level, business scale, business income and business experience have a significant effect on the use of accounting information